GREENHOUSE GAS EMISSIONS FROM POTATO CROP - Singh, Preeti (Potato Journal, 2022)
Human-produced gases including carbondioxide (CO2), methane (CH4), and nitrousoxide (N2O) contribute to the naturalgreenhouse effect. The IntergovernmentalPanel on Climate Change (IPCC) hasconcluded that immediate action is requiredto mitigate the severe risk of humaninducedclimate change posed by thesegases. According to the IPCC (2001) report,agriculture contributes approximately 4% ofglobal carbon emissions from energy use.Agriculture produces emissions througha variety of processes, including entericfermentation and animal waste disposal andfermentation, anaerobic process during ricecultivation, nitrification and de-nitrificationlinked to fertilisation, as well as land clearing,the burning of biomass, fuel wood, andagricultural waste.